PERAN PEREMPUAN DALAM PELESTARIAN LINGKUNGAN HIDUP MENURUT TINJAUAN ISLAM - SYAMSUL QAMAR (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2014)
This paper will try to examine how Islamic ideas about women's role regard to environmental conservation. It is based on assumptions about the reality of society that no longer getting friend with environment. In other words, the environment is not an important consideration in development. As the result, the issue of environment has become a major problem, even become a serious global concern. The Qur'an has informed that Allah is the Preserver or the Conservationist, whereas human are actors who do damage to the ecosystem of the environment, although they do not aware of their and claiming that they are doing environmental conservation. However, the Qur'an asserts that the preservation of the environment requires the active participation of human. This is because of human and environment has a strong mutual symbiosis. The Qur'an commands man to do Salah or ishlah and prohibits to do fasad or ifsad.